The Impact of E-government on the Effectiveness of Anti-corruption Efforts in the Jordanian Governmental Agencies from the Perspective of the Teaching Staff in the Jordanian Public Universities - Al-Zaza , Rawiya Khaled; Al- Khasawneh, Anis Saqer (Jordan Journal of Business Administration, 2023)
This study aimed to investigate the impact of e-government implementation on the effectiveness of anti-corruption efforts in the Jordanian government agencies and to identify the level of both e-government implementation and the effectiveness of anti-corruption efforts in government agencies from the perspective of the academic staff in the Jordanian public universities. A questionnaire was developed and distributed to a convenient non-probability sample from ten public universities. The number of retrieved valid questionnaires amounted to (596). The findings of the study revealed a moderate level of e-government implementation and effectiveness of anti-corruption efforts in government agencies. Notwithstanding the medium level of e-government implementation, the level of speed in providing service came high. The dimensions of the effectiveness of anti-corruption efforts displayed a medium degree; however, a low degree in competence and merit-based government appointments has been yielded. The findings reported a significant medium impact of e-government on the effectiveness of anti-corruption efforts. The study recommended that training programs should be designed and launched to develop the skills of employees and supervisors in charge of e-government applications and spreading the e-government culture through media programs to identify and enhance its applications and utility. Moreover, e-government applications should be designed so that transparency and accountability can be enhanced and employees’ exploitation of their jobs for personal gains can be reduced, if not eliminated. It has been recommended that competence and professional experience should be observed in the appointment to government jobs. The study also recommended that further studies are needed to find out the reasons that lead to citizens’ reluctance or disenchantment to use e-government and find ways and means to raise the awareness of the use of e-government applications in the various branches of government agencies in the governorates.